Thermoplastic Labyrinth Seals Under Rub Impact: Deformation Leakage Mechanisms and High Efficiency Optimization - Fei Ma; Zhengze Yang; Yue Liu; Shuangfu Suo; Peng Su (Lubricants)
Labyrinth seals, extensively used in aerospace and turbomachinery as non-contact sealing devices, undergo accelerated wear and enhanced leakage due to repeated rub-impact between rotating shafts and sealing rings. To address the problem of increased leakage under rub-impact conditions, this research integrates experimental and numerical methods to investigate the deformation mechanisms and leakage characteristics of thermoplastic labyrinth seals. A custom designed rub-impact test rig was constructed to measure dynamic forces and validate finite element analysis (FEA) models with an error of 5.1% in predicting tooth height under mild interference (0.25 mm). Computational fluid dynamics (CFD) simulations further demonstrated that thermoplastic materials, such as PAI and PEEK, displayed superior resilience (with rebound ratios of 57% and 70.3%, respectively). Their post-impact clearances were 4.8–18.3% smaller than those of PTFE and F500. Leakage rates were predominantly correlated with interference, causing a substantial increase compared to the original state; at 0.25 mm interference (reverse flow), increases ranged from 151% (PAI) to 217% (PTFE), highlighting material-dependent performance degradation. Meanwhile, tooth orientation modulated leakage by 0.5–3% through the vena contracta effect. Based on these insights, two optimized inclined-tooth geometries were designed, reducing leakage by 28.2% (Opt1) and 28.1% (Opt2) under rub-impact. These findings contribute to the development of high-performance labyrinth seals suitable for extreme operational environments.